A Facing Terrorist Threats in Peace Operations Through the Prism of International Law - Oktay, Hasan; Poposka, Vesna (International Scientific Journal Vision, 2017)
During the long period of self-determination of the peoples and decolonization struggles, terrorism was perceived as a tactic of the weaker side. Nowadays, it is the tactic of asymmetric warfare, recognized as a key security priority to be addressed by both EU and NATO. Peace operations are conducted in different context and with different mandate. Mandate gives the legal base for enacting, especially for those situations that are not completely legally clear, or urge case by case approach. Peace operations can be divided into two main clusters: peace enforcement missions and peace keeping missions. This qualification gives the predominant notion upon the use of force allowed and the applicable law, but it does not provide answers by itself, especially for dealing with counterterrorist threats that pretty often occur within peace operations.One of the key anchors are the rules for the use of force, since peace operations have pretty often transitional role, and using extra force on micro level can lead to endangering the whole mission on macro level, but there is still lack of comprehensive legal approach. This paper aims to respond the challenge.